Einstein the class hamster saves the library - Tashjian, Janet (Christy Ottaviano Books, Henry Holt and Company, 2015)
When Principal Decker closes Boerring Elementary School's library due to severe budget cuts, Einstein and his friends in Ms. Moreno's class try to reopen it by planning fundraisers, including shooting a video that stars Einstein and Marlon the turtle.